Family friendly policies: assessing family friendliness of Greater Kuala Lumpur/Klang Valley (GKL/KV) areas - Che Abdullah, Ishak; Hashim, Siti Fatimah; Hashim, Habsah; Raja Othman, Raja Norashekin; Nasrudin, Na’asah (Faculty of Administrative Science and Policy Studies, 2023)
Families in the urban areas are facing competing demands of family and work in their day-to-day living. Favourable economic growth and improved facilities in most cities had resulted in the formation of more dual-earner families, where both parents work outside the home. In addition, families in the urban neighbourhoods have gradually lost the informal social ties and kinship support that characterised the rural communities. This paper focuses on essential domains and indicators that contribute to making cities more family-friendly i.e. socio-economic status, children’s care and education. Districts in the Greater Kuala Lumpur/ Klang Valley (GKL/KV) area were evaluated in terms of the level of family friendliness in these domains which consists of eleven indicators. GKL/KV is one of the government’s National Key Economic Areas (NKEA) which aims to transform the area to become among the top-20 most livable metropolis in the world. Analysis was mainly done based on documents review and secondary data that were collected from relevant governmental agencies. Findings revealed that most areas, except for Kuala Lumpur and Putrajaya, scored less than 60 percent. This indicates that most areas need to improve in terms of accessibility, affordability and quality of services related to enhancing the quality of life for families.